Maximizing PV Hosting Capacity in Unbalanced Distribution Systems with High EVs Penetration - Romero, Jairo G. Yumbla [UNESP]; Home-Ortiz, Juan M. [UNESP]; Pinto, Tiago; Mantovani, José R. S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
This paper presents a stochastic scenario-based mixed-integer nonlinear programming (MINLP) model to maximize the photovoltaic-based (PV-based) hosting capacity in unbalanced distribution systems with high penetration of electric vehicles (EVs). The solution of the proposed model determines the optimal operation of voltage regulators (VRs), switched capacitor banks (SCBs), and energy storage devices (ESDs) that allows maximum PV-based penetration in the distribution system. The proposed MINLP model is converted into a mixed-integer linear programming model that can be solved directly using commercial optimization solvers, guaranteeing a finite solution to the problem. Numerical experiments are performed using a 33-node unbalanced distribution system, and results demonstrate that it is possible to increase the PV -based hosting capacity of the system through the optimal adjustment of voltage control devices and ESDs. Besides, results reveal the impact of the high penetration of EVs on the hosting capacity problem.
Keywords: Electric vehicles; energy storage systems; mixed-integer linear programming; PV-based hosting capacity; unbalanced distribution systems; voltage control